Teknetium-99 perteknetat imunoglobulin G manusia sebagai agen radiofarmaseutikal dalam pengesanan inflamasi - Rosnani Hashim,; Shaharuddin Mohd,; Ang, Woan Tze; Wan Hamirul Bahrin Wan Kamal,; Shahrin Abdul Hamid, (penerbit ukm, 2003)
This study was carried out to determine the potential of technetium-99m pertechnetate Human Immunoglobulin G (***Tc.HIgG) as a radiopharmaceutical agent in the detection of inflammation site. Reduced HLgG antibody was found to be stabled at the optimal storage temperatures of -70°C and 0°C and deteriorated at 2 - N°C. The percentage of labeling of HIgG with ***Tc obtained was more than 95%. Biodistribution of ***Tc-HIgG was studied by using Sprague Dawley rats which were injected intramuscularly with turpentine to induce localized inflammation. The biodistribution of ***Tc-HIgG was determined by using immunosintigraphy (scanning) and kill and count method. Immunosintigram obtained after 4 hours post injection showed the clearest image of ***Tc-HIgG biodistribution in the inflamed muscle. The cut and count method also indicated that uptake of ***Tc-HIgG by the inflamed muscle was highest after 4 hours post injection. The pattern of ***Tc localization was different from ***Tc-HIgG. Imaging of inflamed cells using radiopharmaceutical ***Tc-HIgG, Possesses the potential to be used in the diagnosis of infection’inflammation such as in cancer or immunocompromised patients and in assessing patient’s response to the therapy of inflammatory diseases.